Experimental Evidences for Prospect Theory in Vietnam - Dzung, Phan Tran Trung; Tung, Nguyen Xuan; Van, Le Hoang Thu; Thanh, Nguyen Thi Ha (Indian Journal of Finance, 2021)
In the context of growing literature about behavioral finance and experimental research, there is an urgent need to expand this contemporary branch in emerging markets in general and Vietnam in particular. Therefore, this paper aimed at finding evidence of prospect theory in Vietnam using a battery of experimental approach. The objective of experiment design is to understand the economic market and represent almost all risk suffering levels. The research outcomes strengthened arguments of prospect theory in terms of both slope and reference point. This research found evidence for the hypothesis that the utility curve reference point lies in the positive domain. This suggested that in the case of low profitability, investors could still prefer risk over certainty, but they shall be more risk averse as returns are increased. Besides, the relationship between loss aversion and other behavioral biases was also examined, and evidence of strong relation between loss aversion and anchoring and overreaction was found, while there existed no clear correlation between loss aversion and overconfidence. The findings of this paper shed light on current research about behavioral finance, especially about prospect theory in Vietnam, suggesting a pilot approach to find evidence of various behavioral biases that might affect stock market investors’ decisions.